METHOD OF CONSTRUCTION MATRIX CARDANO'S GRIDS FOR COMPRESSION OF INFORMATION - ROZLOMII, INNA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Due to the rapid development of computer technology and the information field, issues related to information security are becoming increasingly important. Knowledge of information security tools is required for the effective organization of the process of transmission and storage of classified information.  The main means of information protection such as encryption, compression and covert transmission of information are present in the article . Information security techniques, including cryptographic data protection systems, play an important role in today's information-filled world. The means of cryptographic data protection, in particular encryption using the  Cardano's encryption grid are list and analyze in the article. Existing mechanisms for reliable storage and transmission of information today do not provide adequate protection. The problem of lack of effective means of information protection is explained by rapid and systematic changes in information technology.The article is devoted to the method of constructing Cardano matrix gratings for compression and hidden data transmission. The developed method is based on the integrated use of existing approaches and methods of information protection. In particular, on the classic cipher of the route permutation – Cardano's encryption grid. Cardano matrix lattice is based on frequency analysis of English text. The algorithm of frequency analysis of the text  and its results are presented in the article. As a result of performing operations of matrix cryptographic transformation of numbers – the rules of distribution of symbols on a lattice are received. In the future, the proposed method will build new algorithms for encrypting information by analogy with the encryption lattice. Also, the created algorithmic models are the basis for building a method of compression and covert data transmission. The methods of information protection considered in the article – encryption, compression and covert transmission, allow us to draw the general conclusion that only their integrated use will ensure an adequate level of protection.
Keywords: texts frequency analysis; redundancy; encoding; grille cipher; information compression; hidden data transmission